Implementation of Duck Egg Hatcher System and Web-Based Monitoring - Dhimas Bagus Adi Saputro; Ritzkal Ritzkal; Bayu Adhi Prakosa (Institute of Computer Science (IOCS), 2020)
Writing this research aims for Web-based egg incubators are tools or machines used to hatch poultry eggs such as ducks and the like, with temperature regulation using NodeMCU ESP 8266 as the control center, DHT11 sensor as temperature sensor, LCD as its appearance, lights and fans. NodeMCU ESP 8266 has an input in the form of a temperature sensor, this sensor will detect 2 temperatures in the incubator and display it on the LCD. This egg incubator uses a fan that functions as a cooler by removing heat in the incubator space and a lamp that functions as a heater, so the incubator will work automatically. How to design and implement a web-based set of duck egg hatching tools and how to display the egg incubator temperature and humidity information on a web connected to an egg incubator suite. By conducting 4 stages of research (i) Analysis of How the System Works and Analysis of Needs (ii) Design Hardware Design, Schematic Design, Database Design, WEB Design, Network Design (iii) Hardware Implementation and Software Implementation (iv) Testing. The results of this research are in the form of designing a duck egg incubator system and web-based monitoring including (i) DHT 11 Sensor Function Testing, Relay Function Testing, WEB Testing. Sensor and WEB testing are in accordance with their functions. The next test is to use the Blackbox on the implementation of the Duck Egg Performance system and Web-Based Monitoring. In this test it is in accordance with its function.